The Construction of Consumers’ Self-esteem through Celebrity Culture - Xenophontos, Eleonora (2011)
This thesis offers a new perspective to consumers and their connection to celebrities. Consumers’ inner psychology, their sense of self and more particularly their self-esteem is examined as to how it can relate to the world of celebrities. The central question to this was whether there is indeed an association between consumers and the luxurious lives of stars. According to this research, celebrity endorsements and negative celebrity images do not fully influence the decision making or the construction of one’s self. Product meaning transfer however, proves to be a key factor in this thesis as celebrity products are thought to represent the celebrities themselves and what they stand for. Self-definition and self-esteem therefore have some part in the perceived meanings that derive from goods. Finally, implications and discussion for further research is also mentioned in the end of this dissertation.